Does Black theology have a role to play in the democratic South Africa? - R. T. H. Dolamo (Acta Theologica)
Black theology was conceived in South Africa in the mid-1960s and flourished from the 1970s, when White supremacy perpetuated by the apartheid state was at its zenith. The struggle against apartheid was aimed mainly at attaining national political liberation so much so that other forms of freedom, albeit implied and included indirectly in the liberation agenda, were not regarded as immediate priorities. Yet two decades into our democracy, poverty, racism, gender injustice, patriarchy, xenophobia, bad governance, environmental degradation, and so on need to be prophetically addressed with equal seriousness and simultaneously, for none of these issues can be left for some time in the future. Using Black Consciousness as a handmaid, Black theology can meaningfully play a role in the democratic South Africa.